2021
DOI: 10.3389/fpsyt.2021.670739
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Studies on Acupuncture Therapy in Depression: A Systematic Review

Abstract: Accumulating studies had been performed using magnetic resonance imaging (MRI) to understand the neural mechanism of acupuncture therapy for depression. However, inconsistencies remain due to differences in research designs and MRI analytical methods. Therefore, we aim to summarize the current MRI research and provide useful information for further research by identifying papers published in English and Chinese about MRI studies on acupuncture for depression up to November 2020. A total of 22 studies met the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 113 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…One was an update of a meta-analysis of EA for post-stroke depression in 2018 (19 trials) (18), which indicated that in comparison with antidepressants, EA has a similar effect in improving depression symptoms and shows better safety in post-stroke depression patients. Another systematic review focused on the neuroimaging effects of acupuncture (including EA) in depression (10 trials of EA) (65). However, that study did not conduct a meta-analysis of efficacy or neuroimaging data of EA for depression because of the limited number of trials and the fact that most of the trials used pre-post designs.…”
Section: Discussionmentioning
confidence: 99%
“…One was an update of a meta-analysis of EA for post-stroke depression in 2018 (19 trials) (18), which indicated that in comparison with antidepressants, EA has a similar effect in improving depression symptoms and shows better safety in post-stroke depression patients. Another systematic review focused on the neuroimaging effects of acupuncture (including EA) in depression (10 trials of EA) (65). However, that study did not conduct a meta-analysis of efficacy or neuroimaging data of EA for depression because of the limited number of trials and the fact that most of the trials used pre-post designs.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright © Yajing Hou PPRS.000637. 6(3).2023 and reshape the microstructure of the white matter fiber bundle in the brain area to reduce the depression scale score of patients [9]. Acupuncture and moxibustion can regulate neurotransmitters, neuroinflammatory cytokines, hypothalamus-pituitary-adrenal axis and hypothalamus-pituitary-gonadal axis to treat depression [10].…”
Section: Psychol Psychother Res Studmentioning
confidence: 99%
“…As previously mentioned, fMRI has been used not only to observe activity in specific brain regions in MDD patients, but also to quantify the brain response induced by acupuncture for MDD in an attempt to illuminate the cerebral mechanism ( 47 ). Importantly, the activity in brain regions such as the ACC, hypothalamus, amygdala and dorsolateral PFC, was found to be positively correlated with the efficacy of acupuncture for MDD, suggesting that acupuncture can improve depressive symptoms by modulating brain networks ( 47–49 ). What this evidence focused on, however, was the cerebral mechanism of manual and electroacupuncture for MDD, and not IA.…”
Section: Introductionmentioning
confidence: 99%